Comparing manual and automated production and picking systems - Cristian Bitterling; Jonas Koreis; Dominik Loske; Matthias Klumpp (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Automated processes play a crucial role, especially when high product quantities are desired. The automation of manufacturing and order picking processes enables companies to reduce the number of manual transports and order fulfillment time. Nevertheless, manual labor remains relevant. This paper analyses the key aspects that define manual and automated labor and their application in manufacturing and order picking systems. Methodology: We conduct a literature review to analyze manual and automated systems in general and for manufacturing and order picking systems. Using field-based research, we provide several real-world use cases where decisions were made in favor of either concept. Finally, we use morphological analysis to distinguish the key elements of both systematics. Findings: Manual labor cannot be substituted when dealing with highly volatile demands or a high variety of products. Moreover, human adaptability and prestidigitation can, thus far, not be automatized. In conclusion, manual as well as automated labor are not always interchangeable. Further, employing manual as well as automated labor is vital to maximize efficiency in manufacturing and order picking. Originality: While studies exist that deal with automated and manual labor, most are directed at automatization of processes, not considering the advantages of manual labor.
urn:nbn:de:gbv:830-882.0200863; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Innovation Management; Technology Management